Pengembangan Buku Ajar Kimia SMA/MA Kelas XI Semester Genap Terinternalisasi Nilai-Nilai Karakter Siswa - Weni Tri Sasmi; Ajat Sudrajat; Iis Siti Jahro (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. This study aims to obtain a chemistry text book of SMA/MA Class XI second semester internalized character values of student. Populasi student learning outcomes of this study were (1) all existing chemistry teacher in Kisaran categorized expert teacher and chemistry lecturer of Universitas Negeri Medan in Medan. (2) all eleventh grade students the second semester of school year 2015/2016 SMA Muhammadiyah 8 in Kisaran. The entire sample was selected by purposive sampling. Samples were determined in this study were (1) a chemistry teacher with a minimum of formal education criteria S1 and teaching experience in schools, a chemistry lecturer of Universitas Negeri Medan with the criteria of formal education S2 at least 5 years, is being actively teach and master the basic chemical materials that are relevant to the material high school chemistry (2) Class XI IPA 1 was given treatment using chemical text book SMA/MA Class XI second semester internalized character values of student based on curriculum 2013. Based on test data analysis requirements the results showed that (1) The results of due diligence analysis chemistry textbook that is based on the standard BSNP amounted to 3.69 visits of criterion validity textbook is quite valid but need to be revised (2) based on the opinions of teachers and lecturers to test the feasibility of chemistry textbook produced in research this meets the standards required by the National Education standards in the amount of 4.41 means that valid and do not need to be revised. (3) based on the opinions of teachers and lecturers to test the feasibility of textbook internalized character values ​​of students in this study meet the standards of assessment rubrics of 4.43 categorized character very well. (4) based on the opinions of students to test the feasibility of textbook internalized character values ​​of students in this study meet the standards of assessment rubrics character is of 4.42 which is considered very good. (5) Improved student learning outcomes using chemistry textbook produced in this study were of 0.69 or 69% were categorized as moderate. (6) Based on data obtained learning outcomes sign value <0.05 (0.002 <0.05) the use of high school chemistry textbook / MA class XI internalized second semester student of character values ​​higher than the KKM. Key words: text book , internalized character values of student